TRAINING OF HEROISM ON PHILOSOPHICAL BASIS - Furkalo, Victoria; Furkalo, Volodymyr (Global Prosperity, 2022)
The article analyzes the issue of educating heroism on philosophical grounds. The philosophical sources on the interpretation of such terms as "hero" and "heroism" are analyzed, and it is determined that the concept of "heroization as a sociocultural phenomenon" is closely related to the human need for heroes and leaders. Changes in the definition of heroism throughout the history of philosophy are considered. It is proven that the analysis of the pattern of people's behavior in the history of the past, the peculiarities of their choices under certain historical conditions helps to form a clear understanding and awareness of various events or phenomena in the young generation, teaches to follow moral norms and rules, describes the main signs for assessing the relationship to various historical facts and military and political figures. In addition, the education of heroism in young people based on historical examples determines the identity of the individual as a consequence of choices and appropriate actions. Thus, in introducing the factor of the past into the process of educating heroism, it is necessary, first of all, to teach the younger generation to think critically, analyze historical events, and develop a tolerance for historical memory and traditions of other communities. That is, it is necessary to build appropriate conditions for the education of heroism at the multicultural level, the creation of educational activities that will unite representatives of different peoples and religions of Ukraine, and the realization of everyone's right to speak the Ukrainian language, culture and education. Thus, based on the study, the conclusion was formed that the modern system of education of heroism based on philosophical synopsis should be focused on forming a worthy, critical and independent personality. In addition, the education of heroism should be the result of the practical implementation of a responsible sense of citizenship as an integrated quality of modern youth. Developing heroism in modern youth, scientific and pedagogical workers should pay attention to the peculiarities of patriotism and the development of the active and responsible civic position of all members of the community. As a result, the education of heroism should be ready for responsible and effective civic action for young people living in Ukraine. Thus, it is determined that the heroism of modern defenders of Ukraine is the best example for the education of the national and patriotic consciousness of young people.